Varied Types - Chesterton, G. K. (Saga Egmont, 2022)
Queens and Emperors, artists and poets, priests and politicians: all are subject to G. K. Chesterton’s collected biographies. ‘Varied Types’ spans the streets of London, travels to the edges of the British empire and doubles back into the depths of history. In a series of essays, Chesterton paints the portraits of England’s most influential figures, from Walter Scott to Lord Tennyson, and favours each with his authoritative wit. This continuation of the collection ‘Twelve Types’ adds eight spectacular essays, featuring Queen Victoria, Alfred the Great, John Ruskin, Elizabeth Barrett Browning, and many more. A superb collection for readers of Chesterton which dives deep into the history of classic English literature.